y=(2x-1)(3x+2)

Simple and best practice solution for y=(2x-1)(3x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=(2x-1)(3x+2) equation:


Simplifying
y = (2x + -1)(3x + 2)

Reorder the terms:
y = (-1 + 2x)(3x + 2)

Reorder the terms:
y = (-1 + 2x)(2 + 3x)

Multiply (-1 + 2x) * (2 + 3x)
y = (-1(2 + 3x) + 2x * (2 + 3x))
y = ((2 * -1 + 3x * -1) + 2x * (2 + 3x))
y = ((-2 + -3x) + 2x * (2 + 3x))
y = (-2 + -3x + (2 * 2x + 3x * 2x))
y = (-2 + -3x + (4x + 6x2))

Combine like terms: -3x + 4x = 1x
y = (-2 + 1x + 6x2)

Solving
y = -2 + 1x + 6x2

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying
y = -2 + 1x + 6x2

See similar equations:

| 4t=16.11-0.0062y | | -x(7)=-40 | | y=(2x-1)(3x-1) | | 4-√-12/4 | | t=16.11-0.0062 | | -7t^2+7t+8t^3-t^3+15t^2-4t= | | 5+8(X-2)=11-7(X-8) | | x(x-6)-x^2-5x-7=0 | | p(x)=(500-x)/20 | | X/100=27/64 | | x(x-6)=x^2+5x+7 | | -4(x-9)=-9x+6 | | -7(t-8)-(t+3)=10 | | X+6y+4z=-13 | | (4x+2)(2x+1)=0 | | x=5000/40/x-10/x | | 4x-9=-18 | | .15x=3800 | | -3x-Y-z=-6 | | 7x+54=9(x+6)-2x | | t-1/4=7/4 | | 5+8(x-2)=7(x-8) | | x*12=44800 | | x*44800= | | -4+4x=4(x-1) | | 8y=16+-2x | | -.25x+x^2=-.1875 | | 2x+8+2x+8+64=180 | | 29/9=100/n | | 140=(n-2)*180/n | | 21=7b | | 4x+5y+2z=x |

Equations solver categories